2015
DOI: 10.1021/acs.cgd.5b00478
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Engineering with Iodoethynylnitrobenzenes: A Group of Highly Effective Halogen-Bond Donors

Abstract: The benefits of employing a 'double activation' strategy for promoting effective practical cocrystal synthesis through halogen bonding was explored in a systematic supramolecular synthetic study of iodoethynylnitrobenzenes, where the positive electrostatic potential on the iodine atom was enhanced through a combination of an sp-hybridized carbon atom and one or more electronwithdrawing nitro groups. Three model compounds, 1-(iodoethynyl)-4-nitrobenzene (4N-I), 1-(iodoethynyl)-3-nitrobenzene (3N-I) and 1-(iodoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 58 publications
2
76
0
Order By: Relevance
“…2b illustrates the pillars of 1, which are held together through two different hydrogen bond acceptors: the urea oxygen (NIJH)⋯O, 2.904(2) Å) and the pyridyl nitrogen (NIJH)⋯N, 3.082(2) Å). 10 Along a single pillar, the oxygen atoms on the macrocyclic assembly of 1 are oriented on opposite sides, one pointing up and the other pointing down. This arrangement results in the available oxygen lone pairs being approximately linear to each other (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2b illustrates the pillars of 1, which are held together through two different hydrogen bond acceptors: the urea oxygen (NIJH)⋯O, 2.904(2) Å) and the pyridyl nitrogen (NIJH)⋯N, 3.082(2) Å). 10 Along a single pillar, the oxygen atoms on the macrocyclic assembly of 1 are oriented on opposite sides, one pointing up and the other pointing down. This arrangement results in the available oxygen lone pairs being approximately linear to each other (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In each co-crystal, CO⋯I interactions ranging from 2.760(4) to 2.853(4) Å were observed that were significantly shorter than the sum van der Waals radii of the atoms involved and are among the shortest reported for neutral organic molecules. 10 To further estimate the strength of the O⋯I interaction, their interaction energies in the co-crystals were calculated by Q-Chem quantum chemistry package in the electronic ground-state using dispersion corrected density function theory (DFT-D). Taking the basis set super position error (BSSE) into account reduces the uncorrected values by 2-3 kJ mol −1 where ΔE represent the uncorrected halogen bond interaction Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…1315 A halogen bond is a short-range RX…YZ interaction, where X is a halogen (typically chlorine, bromine, or iodine) that is part of the molecule RX and YZ is a Lewis base; Y is often an atom, such as oxygen, nitrogen, or sulfur, that has a lone pair. Halogen bonds can be said to be analogous in many ways to hydrogen bonds (of the form RH…YZ).…”
Section: Introductionmentioning
confidence: 99%
“…19 These noncovalent interactions have been observed in protein-ligand complexes, 913 crystal structures of neutral molecules, 1416 and crystals composed of molecular ions. 17, 18 A halogen bond is an interaction of the type RX…YZ, where X is a halogen (chlorine, bromine, or iodine) that is part of the molecule, or molecular ion, RX, and YZ is a Lewis base.…”
Section: Introductionmentioning
confidence: 92%